Accuracy of International Classification of Diseases, 9th Revision, Clinical Modification codes for upper gastrointestinal complications varied by position and age: a validation study in a cohort of nonsteroidal anti‐inflammatory drugs users in Friuli Venezia Giulia, Italy1. (20th August 2013) - Pisa, Federica; Castellsague, Jordi; Drigo, Daniela; Riera‐Guardia, Nuria; Giangreco, Manuela; Rosolen, Valentina; Clagnan, Elena; Zanier, Loris; Perez‐Gutthann, Susana; Barbone, Fabio
ABSTRACT: Purpose: To validate the International Classification of Diseases, 9th Revision, Clinical Modification discharge codes used to identify cases of upper gastrointestinal complications (UGICs) in hospitals of Friuli Venezia Giulia, Italy. Methods: Cohort study on the risk of UGIC in users of nonsteroidal anti‐inflammatory drugs conducted in Friuli Venezia Giulia between 2001 and 2008. Cases were identified through primary and secondary International Classification of Diseases, 9th Revision Clinical specific codes 531 (gastric ulcer), 532 (duodenal ulcer), 533 (peptic ulcer), 534 (gastrojejunal ulcer), and nonspecific code 578 (gastrointestinal hemorrhage). Potential cases were confirmed through hospital chart review. Results: The chart retrieval percentage was 98.4%.The positive predictive value (PPV) was 94.3% for primary codes 531 and 532, 79.5% for code 533, 83.1% for code 534, 40.2% for code 578. The PPV for secondary codes was 34.7% but increased to 88.9% and 79.2% when the primary code was for peritonitis or acute post‐hemorrhagic anemia, respectively. Validation of secondary codes increased case ascertainment by 4.9%. Endoscopy confirmed 79.4% of cases but only 67.2% of those above age 84 years. Conclusions: The PPV was high for specific primary codes and moderate to low for nonspecific primary and secondary codes. The inclusion of confirmed cases identified by nonspecific and secondary codes can be of value in studies that need a complete ascertainment of cases occurring in the study population. In this cohort, not including these cases would underestimate the incidence of UGICs. A potential for case misclassification exists in particular in eldest ages. Copyright © 2013 John Wiley & Sons, Ltd.